Using Qualitative Research in Planning and Evaluating Extension Programs - Lisa A. Guion; Lamont Flowers; David C. Diehl; Debra McDonald (EDIS, 2011)
Qualitative research is a useful tool for understanding extension programs and can complement quantitative methods, because qualitative information, such as interviews, focus groups, ethnography, observation, and case studies, can help faculty gain a rich understanding of the issues they are addressing. This revised 4-page fact sheet provides a brief overview of qualitative research and discusses the ways in which it can be used in planning and evaluating extension programs. Written by Lisa A. Guion, Lamont Flowers, David C. Diehl, and Debra McDonald, and published by the UF Department of Family Youth and Community Sciences, September 2011. (Image by Parul Vora. CC-BY-2.5. Wikimedia Commons)